A design science approach for consultant selection decision support system - Omar, Mohd Faizal; Trigunarsyah, Bambang; Wong, Johnny (2009)
In the past decades, Information System (IS) has been applied in wide and diverse management area. Construction management problem is considered a new and promising area for IS researchers to contribute.Scholars in IS discipline have divided research in two distinct paradigm i.e. behavioral and design science. This paper presented a Design Science Research Methodology (DSRM) for DSS development.The research aims to create an innovative IT artifact to support the decision making for consultant selection problem (CSP).To address the research objectives, three case studies at Malaysian Department of Irrigation and Drainage (DID) are planned to be conducted and integrated in the DSRM framework. It is expected that this research will contribute to the improvement of organizational decision making process for consultant selection involving irrigation and drainage projects.